(untitled) (Research, Society and Development, 2023)
This study focused on confirming the grazing selectivity of sheep, more and less selective, in pasture in New Zealand, under two different phenological stages of forage. Two experiments were conducted: 1) Comparison of selective and non-selective sheep in pasture irrigated with perennial ryegrass and white clover. 2) A comparison was performed with selective and non-selective sheep in pasture with a high rate of senescence composed of perennial ryegrass, barley and barnyard grass. The botanical composition of the forage was studied using the point analysis method. The forage canopy height and forage mass were measured using a disk meter. There was no significant difference between treatments in the variables analyzed. In the first experiment there was a lower clover ratio and increased litter ratio for the botanical composition and point analysis. With regards to height, there was a decrease in grazed clover pasture and grazed ryegrass pasture, as well as the forage mass. In the second experiment the grass ratio, clover height and forage mass decreased and the proportion of litter and grazed grass increased. Despite the differences in the botanical and morphological aspects of the pasture, the selective and non-selective sheep showed similar grazing behavior.